The Relationship Between Early Maladaptive Schemas and Social Anxiety with the Mediation of Emotion Regulation in Female Students - Zadfallah Farshami, Hanieh; Roshandel, Azam (Psychology of Woman Journal, 2024)
Objective: The present study examines the relationship between early maladaptive schemas and social anxiety with the mediation of emotion regulation in female students.Methods and Materials: Considering the objective, this research is classified as applied research. In terms of data type, it is quantitative, and based on its nature, it is descriptive-correlational and utilizes structural equation modeling. The statistical population includes all female students of Islamic Azad University, Lahijan, in the 2023-2024 academic year, totaling 8,000 individuals. The sampling method was multi-stage cluster random sampling. The sample size was determined using Cochran's formula, yielding 367 participants. Data were collected using the Social Anxiety Inventory, Early Maladaptive Schemas Questionnaire, and the Emotion Regulation Questionnaire by Garnefski et al. (2001). The data were analyzed using Pearson correlation coefficient, structural equation modeling, and SPSS version 22 and Smart PLS version 3 software.Findings: The results of the Pearson correlation test indicated a significant relationship between early maladaptive schemas and social anxiety in female students (P < 0.001). Additionally, the results of the structural equation modeling test demonstrated that emotion regulation mediates the relationship between early maladaptive schemas and social anxiety in female students (P < 0.001).Conclusion: There is a significant relationship between early maladaptive schemas and social anxiety with the mediation of emotion regulation in female students.